INFILTRAÇÃO DE ÁGUA NO SOLO CULTIVADO COM MILHO-BRAQUIÁRIA EM ÁREA DE CONTRIBUIÇÃO DE UMA NASCENTE - MENEZES, Roniedison da Silva; MONTEIRO, Felipe das Neves; OZÓRIO, Jefferson Matheus Barros; XIMENES, Thiago Sandim; FERREIRA, Rafael Silva; PANACHUKI, Elói (ANAIS DO ENIC, 2018)
-